Pyruvate Kinase Deficiency Causing Priapism - Shankar, Vinay Hanyalu; Adithya-Sateesh, Bharadwaj; Gousy, Nicole; Ayele, Girma; Petursson, Freyr; Atalay, Rediet; Michael, Miriam (Case Reports in Hematology, 2023)
Pyruvate kinase deficiency (PKD) is an autosomal recessive defect of the enzyme pyruvate kinase (PK) which is involved in catalyzing a reaction that produces ATP in the glycolytic pathway. It is the most common defect of the glycolytic pathway associated with congenital anemia. Patients usually present with signs of chronic hemolytic anemia such as hyperbilirubinemia, splenomegaly, reticulocytosis, and gallstones; the presentation can vary by age. Diagnosis is usually made by demonstration of decreased PK enzymatic activity in a spectrophotometric assay and on the detection of mutations in the PK-LR gene. Management strategies vary from full splenectomies to hematopoietic stem cell transplants with gene therapies with transfusions and administration of PK-activators coming in between. Thromboembolic complications do occur in patients with splenectomy, but there are not much data regarding this for patients with PKD. We present a case of a patient with PKD who demonstrated priapism to be a thromboembolic complication. This differs greatly as priapism has been frequently reported in patients with other chronic hemoglobinopathies such as sickle cell disease, thalassemia, and G6PD with and without splenectomy. While it is still unclear how splenectomies can result in thrombotic events in PKD, there does appear to be a correlation between splenectomies with resultant thrombocytosis with increased platelet adhesion.